Shifting the historical narrative of the Banda Islands; From colonial violence to local resilience - van Donkersgoed, Joëlla (UI Scholars Hub, 2023)
History is a representation of the past based on (written) knowledge which has been passed on from one generation to the next, with a preference given to written sources from a Eurocentric tradition. However, written sources about (former) colonial territories are a product of the colonial system in which they were produced. Acknowledging the biases in these archives, therefore, opens the way for acceptance of other forms of knowledge which were previously deemed “not objective” in Eurocentric historical disciplines. This paper presents several examples from the Banda Islands in Maluku province in Indonesia to attest that, by placing contemporary perceptions of the past and local reiterations of history on an equal pedestal as colonial documentation, we can work towards a more decolonial practice of writing histories. In the case of the Banda Islands, this means a shift from a colonial Eurocentric perspective of its history towards a narration of the past which honours the Bandanese heroes, religion, and resilience.